2023
DOI: 10.3390/healthcare11020269
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Family Medicine-Driven Interprofessional Collaboration on the Readmission Rate of Older Patients

Abstract: Interprofessional collaboration (IPC) for older patient care among family physicians, dentists, therapists, nutritionists, nurses, and pharmacists in the rural hospital care of older patients could improve the hospital readmission rate. However, there is a lack of interventional studies on IPC for improving the readmission rate among Japanese older patients in rural hospitals. This quasi-experimental study was performed on patients >65 years who were discharged from a rural community hospital. The intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…This case highlights the importance of suspecting sepsis and bacteremia in older patients presenting with various symptoms. We believe that medical professionals working in community hospitals, including general physicians, should always be aware of the possibility of fatal sepsis due to various symptoms and respond appropriately to these symptoms to improve the prognosis of older patients in community hospitals [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This case highlights the importance of suspecting sepsis and bacteremia in older patients presenting with various symptoms. We believe that medical professionals working in community hospitals, including general physicians, should always be aware of the possibility of fatal sepsis due to various symptoms and respond appropriately to these symptoms to improve the prognosis of older patients in community hospitals [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that these patients can have multiple coexisting conditions that require thorough diagnostic evaluation [ 16 ]. Collaboration with a multidisciplinary team driven by family physicians can optimize patient outcomes in rural community hospitals [ 17 ]. Therefore, a comprehensive, collaborative approach is necessary to ensure optimal patient care and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration among internal medicine specialists, nutritionists, and physiotherapists was crucial in managing her complications and ensuring adherence to lifestyle changes. This reflects a scholarly approach to clinical care [ 2 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Effectively managing RA is challenging due to the complex role of social determinants of health (SDH). These factors, including socioeconomic status, education, healthcare access, and environmental conditions, significantly affect health outcomes [ 2 ]. In rural areas, where resources and healthcare access are typically restricted, these SDHs create distinct challenges [ 3 ].…”
Section: Introductionmentioning
confidence: 99%